Enfer et catabase : pour une poétique du corps-cadavre dans Quai ouest de Bernard-Marie Koltès - Alexandru N. LAZEA (Eon)
The poetics of the body in Bernard-Marie Koltès is a vast subject, sometimes controversial for politically (in)correct, sociocultural or racial reasons. Koltès places the body at the center of many of his texts as the main theme around which other elements, secondary themes, such as death, money, time or the question of identity, gravitate. In this article, we propose to find another, new meaning for the notion of the body in Quai Ouest (1985). Critics have observed that the corpse floating in the river is not a simple (theatrical) object, but a reflection of a society adrift, encompassing and, at the same time, enclosing the actors. The theories of Georges Dumézil, Gilbert Durand, Mircea Eliade and others will facilitate our mythocritical approach to Bernard-Marie Koltès' text. We conclude with the question of identity, which becomes a constant in this play, given that the societal environment is a mixture of several immigrants, and therefore several nationalities, who have come together in the same mythical space (the hangar).